EVALUASI EFEKTIFITAS JEMBATAN PENYEBERANGAN DIRUAS JALAN Ir. H. JUANDA DI KOTA SAMARINDA - ZULKARNAIN, ILHAM (KURVA S JURNAL MAHASISWA, 2014)
ABSTRACTEVOLUATION EFFECTIVENESS BRIDGE CROSSING IN ROADS Ir. H.JUANDA IN SAMARINDA CITYBy Juanda in Samarinda City.Guided by Dr. Ir. Hendrik Sulistio, MT and Rosa Agustaniah ST., MT.This research aims to determine the effectiveness of bridge crossings for pedestrians, as well as making use of modeling pedestrian bridge crossing.This research was conducted in May 2014 held at the Ir. H. Juanda, village Air Putih, district Samarinda Ulu, province East Borneo. This research uses primary data collection method is by direct survey by distributing questionnaires and secondary data to analyze and collect location data. Analysis used in this research Guttman Scale or is also called Analysis Scale, and Analysis pull of the each mode based on usage modes, in which the use of this analysis is to determine the effect of the relationship between two variables.The results of this research indicate that based on the analysis of Guttman, suitability point below 50% which is 49.65%, so that it can be said that respondents disagreed approaching. Based on the analysis pull of the each mode, Analysis of the pull model of the bridge crossing Y= 8.070+ 0.292X   R² = 0,106. Analysis of the pull model of the availability bridge crossing Y= 0.015+ 0.361X R² = 0,977. Analysis of the pull model of the design ladder bridge crossing Y = 0.063+ 1.804X R² = 0,990. Analysis of the pull model of the security bridge crossing Y = 0.557+ 2.109X R² = 0,985. Analysis of the pull model of the use escalator for bridge crossing Y= 0.038+ 0.136X R² = 0,932. Analysis of the pull